EFISIENSI DAN EFEKTIVITAS PENDISTRIBUSIAN ZAKAT DI BAZNAS KABUPATEN TAPANULI SELATAN - Mega Sri Rahayu; Meutia Fitri (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
The development of the Amil Zakat Institution raises various problems. Lack of understanding of zakat rules is the main factor behind various violations of zakat rules and misuse of zakat distribution. This study aims to determine the efficiency and effectiveness level of the distribution of zakat in Baznas, South Tapanuli Regency. This research uses mixed, qualitative, and quantitative approaches with interview and documentation data collection techniques. The production approach is used to determine the input-output variables, while the assumptions use CRS (Constant Return to Scale) to determine the input-oriented variables. The variables in this study consisted of employee salaries and operating costs as the input-oriented variables, while the output variables consist of the distribution of zakat funds and receipt of zakat funds. The results of this study indicate that the Baznas of South Tapanuli Regency has an efficiency level of 100% for three consecutive years, 2019, 2020, and 2021, while its effectiveness average is 72.76%, which is considered effective (between 70 to 89%).